Subjectivity, communication, economy and bio-politics - Silva Echeto, Víctor (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Biopolitics built a decisive political concept of modern subjectivity. Sobreranía, Nuda vida, homo sacer, performativity, in a parallel way, are paradigms that allow to combine subjectivity, politics and communication. The article carries out a genealogical and archaeological journey through those decisive "images" of modernity that construct, in turn, the contemporary livelihoods of critical theory, political economy and communication.
Keywords: Biopolitics; communication; subjetivity; politics; critical theory